Order parameter symmetry in bismuth (biscco-2223) high tc superconductors (2012)
Electrothermal conductivity measurements as a function of applied magnetic field were performed in order to gain information of the order parameter symmetry (OPS) of Bismuth (BiSCCO-2223) superconducting samples. A correlation between excess electrothermal conductivity and the quasiparticles contribution due mainly to quasiparticles-vortex scattering was assumed. The experimental results of excess electrothermal conductivity determined from electrical resistivity (ρ) and thermopower (S) measurements, carried out at different temperatures close to Tc, can be well described supposing an order parameter symmetry of dx2 - y2 - wave type.